Intellectual structure of knowledge management: a bibliometric analysis of the Journal of Information and Knowledge Management - Nasrallah, Nohade (2021)
The Journal of Information and Knowledge Management (JIKM) published its first issue in 2002 and celebrated its 19th birthday in 2020. This study aims to assess JIKM performance over its lifetime between 2002 and 2020 by extracting data from the Scopus database and using a combined approach of bibliometric and content analysis. More specifically, we evaluate JIKM’s productivity and stature, discuss its performance compared to other journals, and identify key contributing (authors, institutions, and countries), citation pattern, and conceptual structure. The results highlight JIKM’s growing presence, which is reflected in the dual rise of publication activity and accumulated citation. JIKM becomes one of the preeminent journals in the area of knowledge management, with a broad range of scientific actors’ contributions (authors, institutions and countries) from all over the world. Furthermore, using a bibliographic coupling, keywords’ analysis, and co-authorship analysis, we analyse JIKM’s content and identify the most frequent themes discussed. The analysis reveals that JIKM has expanded its scope from knowledge management to a new array of emerging technologies’ topics such as artificial intelligence and data mining. Graphical visualization of similarities (VOSviewer and Rstudio) shows that the major themes published are clustered into four groups, mainly (i) sustainable knowledge, (ii) emerging technologies, (iii) information management, and (iv) organization culture and knowledge sharing.